2014
DOI: 10.1016/j.bcmd.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Eliglustat, an investigational oral therapy for Gaucher disease type 1: Phase 2 trial results after 4years of treatment

Abstract: Eliglustat is an investigational, oral substrate reduction therapy for Gaucher disease type 1 (GD1). Nineteen treatment-naïve patients have now completed 4years of an open-label study (NCT00358150). Mean hemoglobin level and platelet count increased by 2.3±1.5g/dL (baseline: 11.3±1.5g/dL) and 95% (baseline: 68,700±21,200/mm(3)), respectively. Mean spleen and liver volumes (multiples of normal, MN) decreased by 63% (baseline: 17.3±9.5 MN) and 28% (baseline: 1.7±0.4 MN), respectively. Median chitotriosidase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 11 publications
4
50
0
1
Order By: Relevance
“…In clinical phase 2 and 3 studies of previously untreated patients with Gaucher disease type 1, eliglustat induced clinically meaningful improvements in hematological parameters as well as spleen and liver volumes at 9 to 12 months, 8,9 which were maintained at 18 months 10 and after 4 years. 11 Bone mineralization density also continued to improve after 1 to 4 years of eliglustat.…”
Section: Introductionmentioning
confidence: 79%
“…In clinical phase 2 and 3 studies of previously untreated patients with Gaucher disease type 1, eliglustat induced clinically meaningful improvements in hematological parameters as well as spleen and liver volumes at 9 to 12 months, 8,9 which were maintained at 18 months 10 and after 4 years. 11 Bone mineralization density also continued to improve after 1 to 4 years of eliglustat.…”
Section: Introductionmentioning
confidence: 79%
“…This drug has been the subject of several clinical trials for type 1 GD, including, most recently, three phase 3 trials, two of which have been submitted for registration of the drug, and are being continued in extension phases. The 4-year results of the phase 2 trial have recently been published, and they continue to show improvement in key clinical parameters (in 20 of 24 patients) including bones [80]. While it seems to be a better SRT, eliglustat requires long-term experience because of its complex cytochrome P450 metabolism, which may complicate the use of some medications, and because of potential nontrivial cardiotoxicity [81].…”
Section: Therapeutic Approachesmentioning
confidence: 94%
“…61 In our review of studies including Latin American patients undergoing intervention for Gaucher disease, we summarized the studies that had two time points at which patients underwent an intervention, and examined the outcome on skeletal manifestations. These studies 29,30,33,[62][63][64][65][66] showed similar outcomes to the international literature and consensus 59 providing evidence that treatment, especially early intervention, improves skeletal outcomes. (Table 2) …”
Section: Management/treatmentmentioning
confidence: 59%